Innovative Marketing Strategies for the Transformation of Islamic Education - Safitri, Sevia Diana (Journal of Educational Management Research, 2024)
This research aims to explore the integration of technology into the curriculum and the implementation of digital marketing strategies within Islamic educational institutions. This study stems from the need to adapt educational practices to the rapidly changing technological landscape and to enhance the visibility and appeal of these institutions through modern marketing approaches. Employing a qualitative research design with a case study approach, this study seeks to understand the transformation processes occurring within a specific Islamic school. Data were collected through observation, interviews, and documentation. The data analysis was conducted using  interactive model, which involves data reduction, data display, and conclusion drawing. The findings reveal the integration of technology into the curriculum has significantly increased student engagement and learning effectiveness through the use of e-learning platforms and mobile applications. The adoption of digital technologies has enriched learning resources and supported contemporary teaching methods that align with current educational needs. The study also evaluates the effectiveness of the marketing strategies employed, providing insights into their impact on the institution's outreach and growth. The findings are expected to contribute to the understanding of how Islamic educational institutions can successfully combine technology and digital marketing to improve educational outcomes and institutional visibility in a competitive environment.